Systematic video analysis of anterior cruciate ligament injuries in professional female soccer players - Lucarno,S.; Zago, M.; Buckthorpe, M.; Grassi, A.; Tosarelli, F.; Smith, R.; Della Villa, F. (The American Journal of Sports Medicine, 2021)
Background: Female soccer players are particularly susceptible to anterior cruciate ligament (ACL) injuries, accounting for 16% to 43% of the injury burden during the season. Despite the advancements in injury prevention programs, the rate of ACL injuries continues to rise.